Whole-organism and biomarker endpoints in Daphnia magna show uncoupling of oxidative stress and endocrine disruption in phenolic derivatives - Masteling, R. P. (2016)
During the past century, the amount of chemicals released into water bodies has increased, with particular emphasis being attributed to xenobiotics with endocrine disruption properties and/or pro-oxidant effects. Among these, it is possible to identify a specific chemical class, alkylphenols, which are of widespread use, and include a variety of chemicals with multiple uses. Bisphenol A is an important chemical used in industrial production of plastics, and has been extensively described as an endocrine disruptor. Paracetamol is a pharmaceutical compound used in human medicine, known for its therapeutic action but also for its evident pro-oxidant features. Additionally, previous studies have suggested that paracetamol may also exert endocrine disruption. The main goal of this study was to assess the effects of both paracetamol and bisphenol A as endocrine disruptors, and as promoters of oxidative stress and damage, on the freshwater microcrustacean Daphnia magna. The obtained results showed that bisphenol A was capable of altering population traits of exposed organisms, by impairing molting. On the contrary, paracetamol was not causative of any significant change in this parameter, despite having caused extensive oxidative stress.